Identification of Kinship and Characterization of Yellow Bean Local Robusta Coffee - Subroto, Gatot; Avivi, Sholeh; Kusbianto, Dwi Erwin; Suud, Hasbi Mubarak; Savitri, Dyah Ayu (International Journal on Food, Agriculture and Natural Resources, 2024)
— Curahpoh Village, Bondowoso Regency, has the potential to become a center for producing Robusta coffee. The uniqueness is found in several Robusta coffee outliers which produce yellow fruit resembling yellow cattura and yellow bourbon which are only found in Arabica species. A new clone of “yellow robusta coffee” found in Curahpoh Village needs to be characterized and identified for its kinship with existing robusta coffees on the market. It is hoped that the results of this study will become the basis for claims for the first superior new yellow coffee clone in Robusta coffee. This study used several morphological, physiological parameters to characterize these superior clones and identification of kinship with several other Robusta clones using RAPD (Random Amplified Polymorphic DNA). Other robusta clones as a comparison were imported from several community plantations or state-owned enterprises in Bondowoso district and its surroundings. The interim results in this study were that Robusta coffee in Curahpoh village was morphologically identical to BP 44, BP 42, BP 534 and BP358. This hypothesis is supported by the appearance of the leaves which are known to have waves that are quite strong compared to other coffee varieties collected in the trial greenhouse. Morphologically, Robusta coffee in Curahpoh village has similarities/identical with BP 44, BP 42, BP 534 and BP358 on the parameters of leaf number, leaf shape, leaf morphology and fruit color on the plant. Clones BP409, BP42, Sinasense, BP358, BP939, and Propelegitu are coffee clones that are molecularly highly related.